Music makers living legends of Indian classical music - Roy, Ashok (New Delhi Rupa & Co., 2004)
Articles on life and work of 21 Indian classical musicians.
Keywords: Musicians -- India -- Biography; Musicians -- India -- Interviews; Biographical reviews